2017
DOI: 10.1098/rspb.2017.1444
|View full text |Cite
|
Sign up to set email alerts
|

Fragile coexistence of a global chytrid pathogen with amphibian populations is mediated by environment and demography

Abstract: Unravelling the multiple interacting drivers of host-pathogen coexistence is crucial in understanding how an apparently stable state of endemism may shift towards an epidemic and lead to biodiversity loss. Here, we investigate the apparent coexistence of the global amphibian pathogen Batrachochytrium dendrobatidis (Bd) with Bombina variegata populations in The Netherlands over a 7-year period. We used a multi-season mark-recapture dataset and assessed potential drivers of coexistence (individual condition, env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…This corroborates predictions that Bd should be more abundant in wetter areas (Kriger, Pereoglou, & Hero, ; Ron, ), and field studies indicating that Bd outbreaks might be more likely under wet conditions (Bosch et al, ; Lips et al, ). Yet, no published study has linked infection intensity with a reduction in either (a) the size of water basin (hydroshed area) or (b) the density of river networks (however, see Kärvemo et al, ; Spitzen‐van der Sluijs, Canessa, Martel, & Pasmans, ). We found that as hydroshed area increased, infection intensity decreased slightly, suggesting that R. pipiens populations concentrated within a small drainage basin may facilitate the proliferation and transmission of zoospores, as increasing host population density increases transmission rates (Briggs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates predictions that Bd should be more abundant in wetter areas (Kriger, Pereoglou, & Hero, ; Ron, ), and field studies indicating that Bd outbreaks might be more likely under wet conditions (Bosch et al, ; Lips et al, ). Yet, no published study has linked infection intensity with a reduction in either (a) the size of water basin (hydroshed area) or (b) the density of river networks (however, see Kärvemo et al, ; Spitzen‐van der Sluijs, Canessa, Martel, & Pasmans, ). We found that as hydroshed area increased, infection intensity decreased slightly, suggesting that R. pipiens populations concentrated within a small drainage basin may facilitate the proliferation and transmission of zoospores, as increasing host population density increases transmission rates (Briggs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…) and that evaluated effects of Bd load at the individual level in wild populations (Spitzen‐van der Sluijs et al. ). Our approach is unique in part because we treat unobserved infection status and intensity as parameters, rather than using imputation to backfill missing intensity values.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to understand disease impacts in wild populations as a function of load at the individual level have randomly imputed missing infection load data with the observed distribution of load values (Spitzen‐van der Sluijs et al. ). However, random imputation could bias inference if load data are not missing at random, for example, if heavily infected individuals are easier or more difficult to detect than individuals with lower loads.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling approach developed here provides a quantitative means to assess how climate and disease affect demographic rates and population dynamics in hard-to-sample host populations. This builds on previous research that incorporated individual-level covariates in mark-recapture models (Pledger et al 2003, Royle 2008, Gimenez and Choquet 2010, Ford et al 2012), and that evaluated effects of Bd load at the individual level in wild populations (Spitzen-van der Sluijs et al 2017). Our approach is unique in part because we treat unobserved infection status and intensity as parameters, rather than using imputation to backfill missing intensity values.…”
Section: Discussionmentioning
confidence: 99%
“…This presents a major challenge: infection intensity is hard to measure, but may be critical for understanding population dynamics. Previous efforts to understand disease impacts in wild populations as a function of load at the individual level have randomly imputed missing infection load data with the observed distribution of load values (Spitzen-van der Sluijs et al 2017). However, random imputation could bias inference if load data are not missing at random, for example, if load-dependent disease affects detection.…”
Section: Introductionmentioning
confidence: 99%